Echocardiographic parameters indicating left atrial reverse remodeling after catheter ablation for atrial fibrillation - Angelini, Eleonora; Sieweke, Jan-Thorben; Berliner, Dominik; Biber, Saskia; Hohmann, Stephan; Oldhafer, Maximiliane; Schallhorn, Sven; Duncker, David; Veltmann, Christian; Bauersachs, Johann; Bavendiek, Udo (Frontiers in Cardiovascular Medicine, 2023)
Background The echocardiographic parameters total atrial conduction time (PA-TDI duration), left atrial (LA) volume index (LAVI), and LA strain reflect adverse atrial remodeling and predict atrial fibrillation (AF). Objectives The aim of this study was to investigate echocardiographic parameters indicating reverse LA remodeling and potential associations with AF recurrence after pulmonary vein isolation (PVI). Methods This prospective observational study consecutively enrolled patients scheduled for PVI for symptomatic AF. Electrocardiogram (ECG) test and transthoracic echocardiography were performed the day before and after PVI and again 3 months later. AF recurrence was determined by Holter ECG at 3 months, and telephone follow-up at 12 months, after PVI. The parameters of LA remodeling [PA-TDI, LAVI, and LA strain analysis: reservoir strain (LASr), conduit strain (LAScd), contraction strain (LASct)] were determined by transthoracic echocardiography. Results A total of 48 patients were included in the study (mean age: 61.4 ± 12.2 years). PA-TDI significantly decreased the day after PVI compared with the baseline (septal PA-TDI 103 ± 13 vs. 82 ± 14.9 ms, p ≤ 0.001; lateral PA-TDI 122.4 ± 14.8 vs. 106.9 ± 14.4 ms, p ≤ 0.001) and at the 3-month follow-up (septal PA-TDI: 77.8 ± 14.5, p ≤ 0.001; lateral PA-TDI 105.2 ± 16.1, p ≤ 0.001). LAVI showed a significant reduction at the 3-month follow-up compared with the baseline (47.7 ± 14.4 vs. 40.5 ± 9.7, p < 0.05). LASr, LAScd, and LASct did not change after PVI compared with the baseline. AF recurred in 10 patients after PVI (21%). Septal PA-TDI, septal a', and LAVI/a' determined the day after PVI were associated with AF recurrence. Conclusion Changes in echocardiographic parameters of LA remodeling and function indicate that functional electromechanical recovery preceded morphological reverse remodeling of the left atrium after PVI. Furthermore, these changes in echocardiographic parameters indicating LA reverse remodeling after PVI may identify patients at high risk of AF recurrence.